Curing characteristics of chlorosulphonated polyethylene and natural rubber blends - M. MARINOVIC-CINCOVIC; J. BUDINSKI SIMENDIC; G. MARKOVIC; B. RADOVANOVIC (Journal of the Serbian Chemical Society, 2005)
The dependence of the Mooney scorch time and cure index on the blend ratio of chlorosulphonated polyethylene/natural rubber (CSM/SMR 20 CV) and chlorosulphonated polyethylene/chlorinated natural rubber (CSM/Pergut S 40) blends were determined in the temperature range from 120 oC to 160 oC using a Monsanto Mooney viscometer. Semi-efficient vulcanization systems were used for the study. The morphology of the fracture surface of the crosslinked systems was determined by Scanning Electron Microscopy (SEM). The results showed that the scorch time decreased with increasing SMR 20 CV and Pergut S 40 contents. This observation is attributed to the increasing solubility of sulfur, as the content of SMR 20 CV and Pergut S 40 in the composition increased. For temperatures greater than 140 oC, the dependence of the scorch time on blend ratios diminishes, as enough thermal energy is available to overcome the activation energy of vulcanization. The differing curing characteristics of the two blends is explained by the compatibility factor of the respective blend. Morphological analysis of the blends shows a very satisfactory agreement.